EPIDEMIOLOGICAL STUDY ON SALMONELLA SPPISOLATED FROM GOAT IN SOME PROVINCES INMIDDLE OF IRAQ - Y, Afaf; G. M, Alshemmari; S., Mahdi (Iraqi Journal of Science, 2024)
This study aimed to isolate salmonella bacteria from the goats in the fourgoverenent in central Iraq (Babylon, Karbala, Najaf, Baghdad), where the number ofanimals examined 710 head goats in the fields and slaughter houses, 350 samples offeces from 350 animals from thefields while the number of animals at slaughter houses 360 collected from them360 fecal samples and 1440 samples from different organs (the gall bladder , theintestine, mesenteric lymph nodes and spleen) for the purpose of bacterial isolationserological diagnosis.fifty one (51) Salmonella isolates were isolated from the feces and organs at apercentage (2.37%), and was returning to the four serotypes (S.hato, S.typhimurium,S.hadar, S.enteritidis), serotype S.typhimurium constitute the highest percentage ofinfection (70.83%).Percentage of infection in field animals 2.29% and highest in Baghdad (4%) and inslaughter house animals the percentage was 4.44% and highest in Babylon (4.9%),The results showed that during six months of study on the goats examined atslaughter houses, and seven months on goats examined in the fields clear difference,and the higest percentage 8.3% in slaughter house and 4% in fields appeared inmarch.One handerd and ninety three (193) examined animals showed different symptoms(diarrhea , respiratory signs , increased body temperature dullness or more than onesymptom) ,but only 11 animals were found infected with Salmonella, the diarrheaconstitute high percentage (5.08%), while 517 animals appeared normal (withoutsigns). However, 13 animal gave positive results for Salmonella which constitute2.52% .In animals from slaughter houses the percentage of infection were varied inexamined organs and faeces, in bile duct the percentage was 3.06%, 2.57% for eachof the spleen and mesenteric lymph nodes and 1.944% from intestine and feces,while the percentage in feces of field animals showed 2.285%.There was no significant difference between males and females, the percentage ofinfection recorded in females 3.82%, whereas, in males 2.90%. According to the agethe infection percentage was more in animals below six months of age 5.59%.The sensitivity test of the species against antibiotics was studied, the resultsshowed that they are sensitive to (cefotaxime, chloramphenical, trimethoprimesulfamethaxazole, and must species were resistant to ampicillin.